Strength performance of concrete cured in oil spillage contaminated water source in Akwa Ibom State - Ekop, Ifiok Edem; Omongbale, ThankGod Ehiabhi; Asiedet, John Oyoyo (Penerbit Universiti Kebangsaan Malaysia, 2019)
Concrete interacts with substances within its environment. These interactions often have significant effects on the properties of concrete made from ordinary Portland cement. The study assesses the effects of oil spillage contaminated water curing on the performance of concrete. The parameters studied were; water absorption, compressive and flexural strengths at 3, 7, 14, 21 & 28days. The result of the physiochemical analysis of the crude oil contaminated water sourced from the study area indicated an acidic medium with acidity index of 4.77, a Ph value of 5.3, turbidity of 0.6 and it also contained Tetraoxosulphate (vi) acid (H2SO4) of 0.0116 mg/l and Trioxonitrate (v) acid HNO3 of 0.1905 mg/l. Concrete specimens were prepared to 1: 2: 4 mix using a water to cement ratio of 0.55 and cured in the contaminated water for 3, 7, 14, 21 and 28 days. The results obtained indicated a reduction in the compressive and flexural strengths with 15% and 8% for 3days and 36% and 20% for 28days curing ages respectively, these reductions in strength were attributed to the reaction between Portland cement concrete with sulphates and nitrates compounds present in the contaminated water. Increased water absorption of 4.81% after 3days and 8.97% after 28days was also observed.